2014
DOI: 10.1155/2014/491384
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of Two Moderately Cross-Linked Polyethylene Tibial Inserts in a TKR Patient

Abstract: Highly cross-linked polyethylene has become the gold standard in total hip replacement for its wear resistance. Moderately crosslinked polyethylene is now available for total knee replacement (TKR), although concerns about reduced mechanical strength have prevented widespread adoption. The purpose of this report is to describe an unusual case where a patient underwent cruciate retaining TKR using a moderately crosslinked polyethylene tibial insert that went on to fracture twice in the same location across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(13 reference statements)
2
2
0
Order By: Relevance
“…Finally, we had 6 cases of posterior fracture in the HXLPE cohort. We are unaware of these types of fractures being reported in the literature for sequentially annealed HXLPE; however, they appear similar to fractures observed in remelted HXLPE tibial inserts by Teeter et al [28]. While Teeter could not rule out oxidation as a contributing cause of fracture, the Fourier transfer infrared (usually followed by spectroscopy) oxidation data collected in this study likely rules out oxidation as a cause.…”
Section: Discussionsupporting
confidence: 69%
“…Finally, we had 6 cases of posterior fracture in the HXLPE cohort. We are unaware of these types of fractures being reported in the literature for sequentially annealed HXLPE; however, they appear similar to fractures observed in remelted HXLPE tibial inserts by Teeter et al [28]. While Teeter could not rule out oxidation as a contributing cause of fracture, the Fourier transfer infrared (usually followed by spectroscopy) oxidation data collected in this study likely rules out oxidation as a cause.…”
Section: Discussionsupporting
confidence: 69%
“…Although it has been theorized that sequentially annealing polyethylene improves on once-annealed polyethylene by further removing free radicals and does not have the same negative mechanical effects as remelting, a close look at the data indicates this may not be the case. The polyethylene fractures reported by MacDonald et al [12] are similar to those reported by Teeter et al [14] in remelted HXLPE. Our case of early catastrophic wear of sequentially annealed polyethylene further supports the notion that the purported benefits of sequentially annealed polyethylene may not represent an improvement in TKA.…”
Section: Discussionsupporting
confidence: 79%
“…A recent case study highlighted the repeat fracture of a moderately cross-linked tibial insert in one patient, at 16 months and 11 months following revision. 45 Inspection of the inserts highlighted a number of subsurface fatigue cracks. The patient within this case study was reported to be severely obese; therefore, despite no unusual activity being reported, it is likely that the insert underwent high loading.…”
Section: Discussionmentioning
confidence: 99%